Ibero‐Panamerican Federation of Periodontics Delphi study on the trends in diagnosis and treatment of peri‐implant diseases and conditions: A Latin American consensus. Issue 12 (16th May 2021) - Alarcón, Marco Antonio; Sanz‐Sánchez, Ignacio; López‐Pacheco, Andrea; Tavelli, Lorenzo; Galarraga‐Vinueza, Maria Elisa; Schwarz, Frank; Romanelli, Hugo; Peredo, Luis; Pannuti, Claudio Mendes; Javer, Enrique; Vieira, Andrés Felipe; Montealegre, Mauricio; et al.
Abstract: Background: The social diversity, heterogeneous culture, and inherent economic inequality factors in Latin America (LA) justify conducting a comprehensive analysis on the current status and future trends of peri‐implant diseases and conditions. Thus, the aim of this Delphi study was to predict the future trends in the diagnosis and treatment of peri‐implant diseases and conditions in LA countries for the year 2030. Methods: A Latin American steering committee and group of experts in implant dentistry validated a questionnaire including 64 questions divided into eight sections. The questionnaire was run twice with an interval of 45 days, with the results from the first round made available to all the participants in the second round. The results were expressed in percentages and data was analyzed describing the consensus level reached in each question. Results: A total of 221 experts were invited to participate in the study and a total 214 (96.8%) completed the two rounds. Moderate (65%‐85%) to high consensus (≥ 85%) was reached in 51 questions (79.69%), except in the questions dealing with "prevalence", where no consensus was reached. High and moderate consensus was attained for all the questions in three fields (risk factors and indicators, diagnosis and treatment of peri‐implant conditions and deficiencies, and prevention and maintenance). Conclusions: The present study has provided relevant and useful information on the predictions in the diagnosis and treatment of peri‐implant diseases with a high level of consensus among experts. Nevertheless, there is still a lack of agreement in certain domains.